The Low Income of Lecturers Sparks a Worsening Crisis Among University Educators - A. Junaedi Karso (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
According to Law Number 6 of 2023, which stipulates a maximum of 40 working hours per week, a survey conducted by the Kompas Daily Data Journalism Team reveals that the average working hours of lecturers in Indonesia reach 69.64 hours per week throughout 2024. This data highlights a significant discrepancy between the legal provisions and the reality of lecturers' workloads. Despite the law setting limits, many lecturers at Indonesian state universities are facing workloads that far exceed the stipulated working hours. These workloads consist of teaching responsibilities, research, community service, campus administration, and even side jobs, making it clear that the working conditions for lecturers are far from ideal. Moreover, the low salaries, especially for lecturers in private universities, have severe implications not only on individual welfare but also on the broader educational system. The low income of lecturers contributes to a looming teaching crisis on campus, which will inevitably affect the quality of education and lecturer performance. This crisis is further reflected in public sentiment. Google Trend data shows a sharp increase in searches for the phrase